Pengaruh Work-Life Balance terhadap Turnover Intention pada Karyawan PT. X - Aisya Lintang Puri; Lita Ariani; Dicky Listin Quarta (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
High turnover intention remains a significant challenge for companies operating in the mining industry due to its impact on organizational stability and productivity. One factor associated with turnover intention is work-life balance. This study aimed to examine the relationship between work-life balance and turnover intention among production employees at PT. X, a coal mining company in South Kalimantan. The study used a cross-sectional correlational design. A total of 150 employees participated in the study Findings should be interpreted cautiously because participants were recruited through convenience sampling, with a minimum work tenure of one year. Data were collected using the Work-Life Balance Scale adapted from Fisher  and the Turnover Intention Scale adapted from Mobley. The data were analyzed using simple linear regression. The results indicated that work-life balance had a negative and significant effect on turnover intention (R² = 0.21; β = -0.46; p < 0.001). These findings suggest that employees who experience a better balance between work and personal life tend to have lower intentions to leave the organization. Conversely, poor work-life balance increases the likelihood of turnover intention. The findings highlight the importance of organizational policies that support employee well-being, workload management, and work flexibility